PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2015) - Enggar Nursasi (Adbis: Jurnal Administrasi dan Bisnis, 2018)
This research to examine the influence of Good Corporate Governance, which includes managerial ownership, institutional ownership, board composition and audit quality of company value proxied by Tobin's Q. The number of samples in this study are 21 manufacturing companies, especially the consumer goods sector listed on the Indonesia Stock Exchange in 2014 and 2015. Analysis method of this research using Partial Least Square (PLS). The result of the research shows that managerial ownership and board of commissioner have no significant effect to company value, while institutional ownership and audit quality have significant effect to company value.